VR & AR TECHNOLOGIES: OPPORTUNITIES AND APPLICATION OBSTACLES - A. V. Ivanova (Real Economics Publishing House, 2018)
The first attempts to create devices that allow interacting with the imitated reality, as well as augmenting reality with superimposed information, were made at the beginning of the 20th century, the very concept of mixed reality (the “reality-virtuality continuum”), which elements are virtual (VR) and augmented (AR) reality, is quite young (24 years), as well as the market of these technologies. The concept of virtual and augmented reality hasn’t changed radically in the past 30 years, but VR and AR devices and software, and content have gone through a significant evolutionary path, and have already experienced several growth spikes.VR and AR technologies can be applied not only in entertainment and games. Many experts believe that virtual and augmented reality, along with Big Data, cloud technologies, artificial intelligence and some others, will become the key technologies of the 4th industrial revolution. VR and AR also have the potential to become the next big computing platform. Today VR and AR technologies help not only to create conceptually new markets, but also to disrupt existing ones.This article discusses the evolution of the VR and AR concepts and technologies and current market trends. The results of the survey show the key obstacles for the mass distribution of AR and VR technologies: high implementation and operational costs of AR/VR solutions; lack of high-quality content and imperfect devices, implicit effectiveness of their use.Based on the empirical study, a rather extensive list of benefits from using virtual and augmented reality technologies has been drawn up: faster and cheaper learning, training and guiding processes, increase in their efficiency, the reduction of the costs of elements and supplies needed, training support personnel; reducing potential risks to life and health of employees and other people while special training (medical operations and invasive procedures, evacuation, security, rescue in various emergencies) and the related optimization of the compensations; reducing the number of errors and accelerating the processes of assembling, repairing and operating special equipment, searching for information, necessary details, product location in the warehouse; significant reduction of accidents rate, as well as the exploration costs, due to the early identification of malfunctions; accelerating the pace of the designing and prototyping objects, significantly reducing the cost and duration of physical modeling process; improving customer experience, product and trading platforms design, that leads to corresponding increase in volume of sales; improving (simplifying) of communication and increasing its effectiveness.